Penyuluhan dan Pendampingan Pemetaan Partisipatif di Kecamatan Anggeraja Kabupaten Enrekang - Ihsan Latief; Abdul Rachman Rasyid; Laode Mughammad Asfan Mujahid; Sri Aliah Ekawati; Suci Anugrah Yanti (Faculty of Engineering UNHAS, 2019)
Maps are presented to provide information in the form of boundaries, facilities, buildings, land use and roads. Regional boundaries are one element of the village map so that it needs to be mapped in detail as a document in development planning. Enrekang Regency, which has a majority of its elders as protected areas, is still very limited in the ownership of mapping documents. The community still does not have knowledge about this mapping so that the problem of regional boundaries, regional boundaries and land use limits is still a trigger for problems in the community. Participatory mapping is a method that is needed in order to provide spatial information so that the mapping process and the resulting map are aimed at the interests of the community. In this case, counseling and mentoring activities are the beginning of the development of competence and capacity for the community in making mapping documents in Enrekang District. It is expected that this community service activity will continue in partnership activities between Unhas and the Enrekang District Government, both in training, formal education in regional and city development master programs, and assistance in planning and implementing the development of Enrekang Regency, in line with the tridharma activities of higher education.